TINGKAT KEPUASAN PADA PASIEN LANJUT USIA TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKEMAS IDI RAYEUK - Fia Dewi Auliani; Denni Hermartin (Jurnal Sains Riset, 2021)
Elderly is someone who is old and experiences such as biological, physical, psychological, and social changes. The percentage of elderly in Indonesia has increased from year to year. In 2018, there are 9,27 % or about 24,49 million elderly from the entire population Improvement of services for the elderly must be increased along with the increasing number of elderly from year to year through improving the quality of health services that will have an impact on patient satisfaction. This research aims to analyze the correlation between the level of satisfaction in elderly patients with the quality of health services at the Community Health Center of Idi Rayeuk.There were 50 respondents as samples in this study using accidental sampling techniques. The research design was a descriptive cross sectional-analytic approach. The research result based on Kolmogorov Smirnov showed a p-value of 0,000 0.05. This indicates that there is an intense correlation between satisfaction on senior citizens on the quality of the services at the Community Health Center of Idi Rayeuk. The recommendations from this study are expected to be a reference for further research regarding service quality and patient satisfaction.Keywords: Quality of Service, Satisfaction level